PENGARUH KECENDERUNGAN BELAJAR ONLINE SELAMA COVID-19 TERHADAP MINAT BELAJAR ANAK DI KAMPUNG PASULUHAN KECAMATAN WALANTAKA KOTA SERANG - E. Nita Prianti; Susilawati (Bajang Institute, 2022)
This study aims to determine the effect of online learning tendencies during Covid-19 on children's learning interest in Pasuluhan Village, Walantaka District, Serang City. The background to this problem is the low interest in learning children online, causing low learning achievement for children, lack of parental assistance, online learning is considered less effective, internet access is inadequate. The formulation in this study is